Evaluation of Liver Function Tests and Histopathological Severity in Patients Undergoing Hepatic Resection for Benign and Malignant Lesions: A Cross-Sectional Study - Muhammad Tariq Hamayun Khan, Farhan Abbas Baloch, Shahzada Amir Ahmed Babar, Qandeel Abbas Soomro, Mumtaz Lakho, Ratan Kumar Ramani (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Accurate preoperative evaluation of liver function is essential for predicting surgical risk and guiding perioperative management in patients undergoing hepatic resection. Liver function tests (LFTs) provide a non-invasive biochemical snapshot of hepatic status, while histopathological analysis offers definitive insights into tissue-level disease severity. However, the relationship between these parameters remains underexplored, especially in the context of benign versus malignant hepatic lesions. Objective: To assess the association between preoperative liver function test parameters and histopathological severity in patients undergoing hepatic resection for benign and malignant liver lesions. Methods: A cross-sectional study was conducted on 70 patients who underwent hepatic resection. Patients were categorized into benign and malignant groups based on postoperative histopathological diagnoses. Preoperative LFTs including ALT, AST, ALP, bilirubin, albumin, and INR were recorded and compared between groups. Histopathological parameters such as fibrosis stage, necrosis, steatosis, and inflammatory infiltrate were evaluated and statistically correlated with LFT values using Pearson correlation and group comparisons. Results: Of the 70 patients, 32 had benign and 38 had malignant hepatic lesions. Patients with malignant lesions had significantly elevated ALT (74.2 ± 23.1 vs. 46.8 ± 15.7 IU/L), AST (69.7 ± 20.4 vs. 41.9 ± 12.6 IU/L), ALP (222.6 ± 61.3 vs. 182.4 ± 43.8 IU/L), and INR (1.27 ± 0.18 vs. 1.06 ± 0.13), and lower albumin levels (3.52 ± 0.44 vs. 4.11 ± 0.41 g/dL) compared to benign cases (all p < 0.05). Histologically, malignant lesions exhibited higher frequencies of advanced fibrosis, necrosis, and inflammatory activity. ALT, AST, and INR positively correlated with necrosis and fibrosis, while albumin showed a significant inverse correlation. Conclusion: Preoperative liver function tests, particularly AST, ALT, albumin, and INR, demonstrate significant correlation with histopathological severity in hepatic lesions. These routinely available biochemical parameters can serve as useful predictive tools for assessing underlying tissue damage, especially in patients with suspected malignancy. Their incorporation into preoperative assessment protocols may enhance clinical decision-making and surgical planning. Keywords: Liver function tests, hepatic resection, histopathology, benign liver lesions, malignant liver tumors, fibrosis, necrosis, biochemical markers.